2015
DOI: 10.1109/led.2015.2436213
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Temperature Sensor Based on 4H-SiC Schottky Diodes

Abstract: A high-performance temperature sensor based on coupled 4H-SiC Schottky diodes is presented. The linear dependence on temperature of the difference between the forward voltages appearing on two diodes biased at different constant currents, in a range from 30°C up to 300°C, was used for temperature sensing. A high sensitivity of 5.11 mV/°C was measured. This is, to the best of our knowledge, the first experimental result about a proportional-to-absolute-temperature sensor made with SiC diodes, showing both a goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…In this work we analyze a large set of experimental data showing that the V F vs. T J relationship can be optimized to perform an excellent linearity, allowing to easily and reliably measure the internal device temperature, without involving an external temperature sensor. The technique is developed starting from previous studies carried out on diodes of various types and sizes [28]- [31], and is here shown to be perfectly suitable also for LEDs, and further improved to make the measurement faster and the measuring circuit simpler. It is worth noting that a highly linear dependence in a wide temperature range allows the simplest experimental pre-calibration procedure of the device, which can be in fact carried out at just two temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we analyze a large set of experimental data showing that the V F vs. T J relationship can be optimized to perform an excellent linearity, allowing to easily and reliably measure the internal device temperature, without involving an external temperature sensor. The technique is developed starting from previous studies carried out on diodes of various types and sizes [28]- [31], and is here shown to be perfectly suitable also for LEDs, and further improved to make the measurement faster and the measuring circuit simpler. It is worth noting that a highly linear dependence in a wide temperature range allows the simplest experimental pre-calibration procedure of the device, which can be in fact carried out at just two temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…All of these reported simple devices show low sensitivities and relatively poor linearity. In a recent work, for the first time, a proportional to absolute temperature (PTAT) sensor was developed, based on two identical 4H-SiC Schottky diodes biased with different currents [10]. However, there have hitherto been no reports on sensitivity variations in SiC junction barrier Schottky (JBS) devices.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature sensors are required in virtually all monitoring applications, irrespective of investigated settings [1]. As advancements in regulations targeting the minimization of industrial impact on the environment are carried out, precise temperature control and energy efficiency have become essential research topics, which exert ever-growing standards from temperature sensors [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19]. This aspect works in tandem with the fact that most industrial processes demand careful monitoring of temperature levels in order to ensure optimal quality and yield [1,6].…”
Section: Introductionmentioning
confidence: 99%